MIGRASI DAN JARINGAN EKONOMI SUKU BUGIS DI WILAYAH TANAH BUMBU, KERESIDENAN BORNEO BAGIAN SELATAN DAN TIMUR, 1930-1942 - Mansyur Mansyur (Jurnal Sejarah Citra Lekha, 2016)
The Bugis migration to Tanah Bumbu, Afdeeling Pasir en de Tanah Boemboe, Residentie Borneo’s Zuid en Oosterafdeeling continued until the early decades of the 20th century, especially in 1930-1942. It was indirectly indicates how strong economic motives of the Bugis. In an effort to survive in the midst of economic depression or malaise, Bugis migrants "creates" economic adaptation strategy to establish a network of fisheries Ponggawa (skipper) Bugis in the early 1930's. Most migrant Bugis also tried farmer (bahuma) for copra and coconut planting. Plantation crops are suitable and almost the same as plantation crops in South Sulawesi. In addition, in the field of marine migrant boat Bugis also developed business people to serve the marine transportation. This study uses the history of the historical method, which is a method to test and analyze critically the recording and relics of the past. The historical method comprises step heuristics, criticism of sources (external and internal), interpretation and historiography.